Oxidative Stability of Acylated and Hydrogenated Ricinoleates Using Synthetic and Natural Antioxidants - F. Murilo T. Luna; Davi Costa Salmin; Vanessa S. Santiago; Francisco J. N. Maia; Francisco O. N. Silva; Selma E. Mazzetto; Célio L. Cavalcante (Journal of Chemistry)
As increasing environmental policies constrains are imposed, the demand for biodegradable products also increases. Although vegetable oils present some properties that favor its use for formulation of a bio-based lubricant, its poor resistance to oxidation hinders its application as such. In this study, the thermo-oxidative stability of bio-based products was compared to petroleum-based lubricants and vegetable oils through the PetroOXY method. Chemical modifications in the ricinoleic acids were carried out using long-chain alcohols in esterification reactions. Acetates were obtained from ricinoleates with and without hydrogenation steps. Additionally, commercial antioxidants and phenolic compounds (saturated and unsaturated cardanol) obtained from cashew nut shell liquid were added to the synthesized samples with higher induction times. The results show that the chemically modified bio-based products exhibited improved oxidative stability (up to 6 times) and depressed pour point (−42°C) when compared to pure castor oil. Overall, the addition of antioxidants increased from 6 to 20 times the oxidative stability of the bio-based products. Propyl gallate and saturated cardanol showed higher efficiency for retarding the oxidative process of bio-based samples than the commercial antioxidants.